Environment-friendly sponge and application thereof
By adding antibacterial microcapsules and modified hybrid nanoparticles to the polyurethane sponge, the problem of insufficient yellowing resistance of the polyurethane sponge under light and thermal conditions is solved, and the efficient mite removal, antibacterial and aging resistance of the material is achieved. Expand its application in furniture and other fields.
Patent Information
- Application Number
- CN202411589350.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing polyurethane sponges are prone to yellowing and brittle under the action of light and heat, and have poor weather resistance, making them difficult to meet the environmental protection, comfort, beauty and durability requirements of furniture, clothing and other fields for materials.
Add antibacterial microcapsules and modified hybrid nanoparticles to the polyurethane foam sponge to improve mite removal effect, antibacteriality and aging resistance. Antibacterial microcapsules are prepared by interfacial polymerization, containing benzyl benzoate and 1,2-benzisothiazole-3-one, which have good UV absorption properties and thermal stability; modified hybrid nanoparticles are passed through triazine derivatives Grafting nanotitanium dioxide-nano zinc oxide hybrid particles improves the thermal stability and light stability of the material.
It significantly improves the mite removal effect and antibacterial properties of environmentally friendly sponges, enhances their yellowing resistance under light and thermal conditions, extends their service life, and expands their application range in furniture and other fields.
Smart Images

Figure BDA0005125154190000061 
Figure BDA0005125154190000091 
Figure BDA0005125154190000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyurethane sponge material preparation, and in particular relates to an environmentally friendly sponge and application thereof. Background Art
[0002] Mattresses are common items in people's home life and play a very important role in people's daily life. Sponge mattresses are a common type on the market. Sponge mattresses are usually made of polyurethane. Polyurethane sponges have the advantages of softness, low density, good resilience, and small compression permanent deformation. They are widely used in furniture, clothing, decorative materials and other fields. Ordinary polyurethane sponge products have poor weather resistance. When exposed to sunlight, they will cause chemical reactions under the action of light and heat, causing the material to turn yellow, become brittle, and the mechanical properties to decrease, and even lose their use value. Since the industrialization of polyurethane, the photooxidation and degradation of foams have always been a hot topic of research and concern in the polyurethane industry. Especially in the fields of furniture, clothing, decorative materials, etc., sponge materials are required to be environmentally friendly and comfortable, as well as beautiful and durable. This has high requirements for the yellowing resistance of polyurethane sponges under light and heat conditions. Therefore, it is of great practical value to develop polyurethane sponge materials with excellent yellowing resistance, environmental protection and comfort.
[0003] At present, light stabilizers and heat stabilizers, whitening agents, and nanoparticles are often added in the preparation method of polyurethane sponges. The working principle of light stabilizers and heat stabilizers is to prevent the breakage and degradation process of polyurethane macromolecular chains. The working principle of whitening agents is that under light conditions, the material can reflect white light, and the material appears white when observed by the naked eye. Nanoparticles (TiO 2 , ZnO) has ultraviolet activity characteristics and can effectively absorb ultraviolet rays of a certain band, thereby slowing down the radiation effect of ultraviolet rays on sponge materials. It is often used in yellowing-resistant foams, but the compatibility of this material with the foaming system is poor, which will cause a series of problems such as irregular pores and collapsed bubbles. At the same time, this additive still has considerable limitations in improving the yellowing resistance performance, so it has not been widely promoted in industrial production. In addition, existing polyurethane sponges usually do not have antibacterial effects, and are prone to breeding bacteria and mites after long-term use, which limits the application of polyurethane sponges in furniture, clothing and other fields. Summary of the invention
[0004] In order to solve the deficiencies mentioned in the above-mentioned background technology, the purpose of the present invention is to provide an environmentally friendly sponge and its application. Antibacterial microcapsules are added to the polyurethane foam sponge to effectively improve the mite removal effect and antibacterial properties of the environmentally friendly sponge. At the same time, modified hybrid nanoparticles are added to improve the aging resistance of the environmentally friendly sponge, thereby increasing the application range of the polyurethane foam sponge in furniture products such as mattresses.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] An environmentally friendly sponge comprises the following raw materials in parts by weight: 110-150 parts of polyether polyol, 60-80 parts of diphenylmethane diisocyanate, 2-8 parts of a crosslinking agent, 5-10 parts of a pore opening agent, 3-5 parts of a foaming agent, 0.1-0.5 parts of a foam stabilizer, 1.5-2.5 parts of an amine catalyst, 5-10 parts of antibacterial microcapsules, and 10-15 parts of modified hybrid nanoparticles;
[0007] The antibacterial microcapsules are polyurea microcapsules containing benzyl benzoate and 1,2-benzisothiazol-3-one prepared by interfacial polymerization;
[0008] The modified hybrid nanoparticles are nano-titanium dioxide-nano-zinc oxide hybrid particles grafted with triazine derivatives, and the triazine derivative molecules contain hindered phenol structures and siloxane structures.
[0009] More preferably, the polyether polyol has a number average molecular weight of 600 to 800, a functionality of 3, and a hydroxyl value of 230 to 250 mgKOH / g.
[0010] Further preferably, the cross-linking agent is diethanolamine, the cell opening agent is polyether polyol S25K, the foam stabilizer is silicone oil L-580, the amine catalyst is compounded by amine catalyst A33 and amine catalyst A1, and the foaming agent is deionized water.
[0011] Further preferably, the method for preparing the antibacterial microcapsules comprises the following steps:
[0012] (1) Gum arabic is uniformly dispersed in deionized water and a stable aqueous phase is formed by magnetic stirring, and benzyl benzoate, 1,2-benzisothiazol-3-one and isophorone diisocyanate are mixed at room temperature to form an oil phase;
[0013] (2) pouring the oil phase into the water phase for emulsification treatment, emulsifying by high-speed shearing at 6000-8000 r / min for 8-10 min to form a uniform water-in-oil emulsion, and then heating the obtained emulsion to 30° C. while continuously stirring, and then adding 1,6-hexanediamine;
[0014] (3) keeping the mixture at 30° C. for 20 to 30 minutes, then raising the temperature to 60° C. for reaction for 2 to 4 hours, and after the reaction, washing the mixture with 20% Vol ethanol aqueous solution and deionized water in sequence, followed by filtering and freeze-drying to obtain the antibacterial microcapsules.
[0015] More preferably, the mass ratio of gum arabic, benzyl benzoate and 1,2-benzisothiazol-3-one is 1:3.4-3.8:0.2-0.6.
[0016] Further preferably, the method for preparing the modified hybrid nanoparticles comprises the following steps:
[0017] A. Add nano titanium dioxide powder to ionized water, ultrasonically disperse for 5 to 10 minutes, then add zinc nitrate hexahydrate and sodium dodecylbenzene sulfonate, continue ultrasonically dispersing for 40 to 60 minutes, add 3wt% urea solution, and heat at 80°C for 1 to 3 hours. After filtering and washing the product, place it in a 350°C tubular furnace and calcine it for 3 to 5 hours to obtain nano titanium dioxide-nano zinc oxide hybrid particles;
[0018] B. Add cyanuric chloride to tetrahydrofuran and triethylamine under nitrogen atmosphere, stir to dissolve cyanuric chloride, then uniformly add 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionohydrazide, react in an ice bath for 6-8 hours after the addition is completed, then add N-(2-aminoethyl)-3-aminopropyltriethoxysilane dropwise to the reaction system, then heat up to 60°C at a rate of 2-4°C / min, keep the temperature for 3-5 hours, cool after the reaction is completed, remove triethylamine hydrochloride by suction filtration, remove tetrahydrofuran by reduced pressure distillation, wash with deionized water 3-5 times, add ethyl acetate to the separated organic phase, dry and filter, and distill the filtrate under reduced pressure to obtain a triazine derivative;
[0019] C. Add nano-titanium dioxide-nano-zinc oxide hybrid particles to an ethanol aqueous solution, ultrasonically disperse for 10 to 15 minutes, adjust the solution pH to 4 with a hydrochloric acid aqueous solution, then slowly add the triazine derivative to the above dispersion, continue ultrasonically dispersing for 5 to 10 minutes, heat to 80°C and keep warm for 3 to 5 hours, filter after cooling, wash, and dry to obtain the modified hybrid nanoparticles.
[0020] Further preferably, the mass ratio of nano titanium dioxide, zinc nitrate hexahydrate and sodium dodecylbenzene sulfonate is 1:5 to 6:3.
[0021] More preferably, the molar ratio of cyanuric chloride, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionohydrazide, and N-(2-aminoethyl)-3-aminopropyltriethoxysilane is 1:2:1-2.
[0022] Further preferably, the preparation method of the environmentally friendly sponge comprises the following steps: polyether polyol, cross-linking agent, pore opening agent, foaming agent, foam stabilizer, amine catalyst, antibacterial microcapsule, and modified hybrid nanoparticles are uniformly stirred using a high-speed disperser, and then diphenylmethane diisocyanate is added and stirred quickly, and then poured into a constant temperature mold for foaming, and the mold is opened after 20 to 30 minutes to obtain the environmentally friendly sponge.
[0023] The invention discloses an application of an environmentally friendly sponge. The environmentally friendly sponge is used in a slow-rebound sponge mattress and has a good antibacterial and mite-removing effect.
[0024] Beneficial effects of the present invention:
[0025] The environmentally friendly sponge of the present invention adds antibacterial microcapsules to the polyurethane foam sponge, which effectively improves the mite removal effect and antibacterial property of the environmentally friendly sponge, and at the same time adds modified hybrid nanoparticles to improve the aging resistance of the environmentally friendly sponge. Among them, the polyurea-based antibacterial microcapsules synthesized by the interfacial polymerization method of the present invention have a high encapsulation rate of benzyl benzoate and 1,2-benzisothiazol-3-one, and at the same time, the microcapsule wall material has good ultraviolet absorption performance and thermal stability, which can effectively protect the core material, and the encapsulated microcapsules have good sustained release performance, and can have a long-term mite removal effect and antibacterial property. The modified hybrid nanoparticles of the present invention are prepared from triazine derivatives by nucleophilic substitution reaction of cyanuric chloride, 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl hydrazide and N-(2-aminoethyl)-3-aminopropyl triethoxysilane, so that the triazine derivative molecules contain hindered phenol structure and siloxane structure, which are then grafted on the surface of nano titanium dioxide-nano zinc oxide hybrid particles, thereby improving the dispersibility of the hybrid nanoparticles in the polymer, and at the same time, due to the presence of the hindered phenol structure, the material is given good thermal stability. In addition, the hybrid nanoparticles themselves have good light stability, and can also improve the aging resistance of the material. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Example 1
[0028] An antibacterial microcapsule, wherein the antibacterial microcapsule is a polyurea microcapsule containing benzyl benzoate and 1,2-benzisothiazol-3-one prepared by an interfacial polymerization method, and the preparation method thereof comprises the following steps:
[0029] (1) 2.0 g of gum arabic was uniformly dispersed in 80 ml of deionized water and stirred by magnetic force to form a stable aqueous phase. 7.1 g of benzyl benzoate, 0.8 g of 1,2-benzisothiazol-3-one and 1.3 g of isophorone diisocyanate were mixed at room temperature to form an oil phase;
[0030] (2) pouring the oil phase into the water phase for emulsification treatment, emulsifying by high-speed shearing at 7000 r / min for 9 minutes to form a uniform water-in-oil emulsion, and then heating the obtained emulsion to 30° C. while continuously stirring, and then adding 1.8 g of 1,6-hexanediamine;
[0031] (3) keeping the mixture at 30° C. for 25 min, then raising the temperature to 60° C. for reaction for 3 h, and after the reaction, washing with 20% Vol ethanol aqueous solution and deionized water in sequence, followed by filtering and freeze-drying to obtain the antibacterial microcapsules.
[0032] Example 2
[0033] A modified hybrid nanoparticle, wherein the modified hybrid nanoparticle is a nano-titanium dioxide-nano-zinc oxide hybrid particle grafted with a triazine derivative, wherein the triazine derivative molecule contains a hindered phenol structure and a siloxane structure, and has the structural formula:
[0034]
[0035] The preparation method of the modified hybrid nanoparticles comprises the following steps:
[0036] A. Add 0.5 g of nano titanium dioxide powder to 200 ml of ionized water, ultrasonically disperse for 8 min, then add 2.8 g of zinc nitrate hexahydrate and 1.5 g of sodium dodecylbenzene sulfonate, continue ultrasonically dispersing for 50 min, add 3 wt % of urea solution, and heat at 80 ° C for 2 h. After filtering and washing the product, place it in a 350 ° C tube furnace and calcine it for 4 h to obtain nano titanium dioxide-nano zinc oxide hybrid particles;
[0037] B. Add 3.7 g of cyanuric chloride to 30 ml of tetrahydrofuran and 30 ml of triethylamine under a nitrogen atmosphere, stir to dissolve the cyanuric chloride, then uniformly drop 5.8 g of 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionohydrazide, react in an ice bath for 8 h after the dropwise addition is completed, then drop 5.1 g of N-(2-aminoethyl)-3-aminopropyltriethoxysilane into the reaction system, then heat at a rate of 3°C / min to 60°C, keep the temperature for 4 h, cool after the reaction is completed, remove triethylamine hydrochloride by suction filtration, remove tetrahydrofuran by reduced pressure distillation, wash with deionized water 3 to 5 times, add ethyl acetate to the separated organic phase, dry and filter, and distill the filtrate under reduced pressure to obtain a triazine derivative;
[0038] C. Add 10.5 g of nano-titanium dioxide-nano-zinc oxide hybrid particles to 100 ml of 95% Vol ethanol aqueous solution, ultrasonically disperse for 12 min, adjust the solution pH to 4 with hydrochloric acid aqueous solution, then slowly add the triazine derivative to the above dispersion, continue ultrasonic dispersion for 8 min, heat to 80° C. and keep the reaction for 4 h. After cooling, filter, wash and dry to obtain the modified hybrid nanoparticles.
[0039] Example 3
[0040] An environmentally friendly sponge comprises the following raw materials in parts by weight: 110 parts of polyether polyol, 80 parts of diphenylmethane diisocyanate, 2 parts of diethanolamine, 10 parts of polyether polyol S25K, 3 parts of deionized water, 0.5 parts of silicone oil L-580, 1 part of catalyst A33, 0.5 parts of amine catalyst A1, 10 parts of antibacterial microcapsules, and 10 parts of modified hybrid nanoparticles; the antibacterial microcapsules are polyurea microcapsules containing benzyl benzoate and 1,2-benzisothiazol-3-one prepared by interfacial polymerization in Example 1; the modified hybrid nanoparticles are triazine derivative grafted nano-titanium dioxide-nano-zinc oxide hybrid particles prepared in Example 2;
[0041] The preparation method of the environmentally friendly sponge comprises the following steps: polyether polyol, diethanolamine, polyether polyol S25K, deionized water, silicone oil L-580, catalyst A33, amine catalyst A1, antibacterial microcapsules, and modified hybrid nanoparticles are uniformly stirred using a high-speed disperser, and then diphenylmethane diisocyanate is added and stirred quickly, and then poured into a constant temperature mold, molded and foamed, and the mold is opened after 20 minutes to obtain the environmentally friendly sponge.
[0042] Example 4
[0043] An environmentally friendly sponge comprises the following raw materials in parts by weight: 150 parts of polyether polyol, 60 parts of diphenylmethane diisocyanate, 8 parts of diethanolamine, 5 parts of polyether polyol S25K, 5 parts of deionized water, 0.1 parts of silicone oil L-580, 1.5 parts of amine catalyst A33, 1 part of amine catalyst A1, 5 parts of antibacterial microcapsules, and 15 parts of modified hybrid nanoparticles; the antibacterial microcapsules are polyurea microcapsules containing benzyl benzoate and 1,2-benzisothiazol-3-one prepared by interfacial polymerization in Example 1; the modified hybrid nanoparticles are triazine derivative grafted nano-titanium dioxide-nano-zinc oxide hybrid particles prepared in Example 2;
[0044] The preparation method of the environmentally friendly sponge comprises the following steps: polyether polyol, diethanolamine, polyether polyol S25K, deionized water, silicone oil L-580, amine catalyst A33, amine catalyst A1, antibacterial microcapsules, and modified hybrid nanoparticles are uniformly stirred using a high-speed disperser, and then diphenylmethane diisocyanate is added, stirred quickly, poured into a constant temperature mold, and molded for foaming, and the mold is opened after 30 minutes to obtain the environmentally friendly sponge.
[0045] Example 5
[0046] An environmentally friendly sponge comprises the following raw materials in parts by weight: 130 parts of polyether polyol, 70 parts of diphenylmethane diisocyanate, 5 parts of diethanolamine, 8 parts of polyether polyol S25K, 4 parts of deionized water, 0.3 parts of silicone oil L-580, 1.5 parts of amine catalyst A33, 0.5 parts of amine catalyst A1, 8 parts of antibacterial microcapsules, and 12 parts of modified hybrid nanoparticles; the antibacterial microcapsules are polyurea microcapsules containing benzyl benzoate and 1,2-benzisothiazol-3-one prepared by interfacial polymerization in Example 1; the modified hybrid nanoparticles are triazine derivative grafted nano-titanium dioxide-nano-zinc oxide hybrid particles prepared in Example 2;
[0047] The preparation method of the environmentally friendly sponge comprises the following steps: polyether polyol, diethanolamine, polyether polyol S25K, deionized water, silicone oil L-580, amine catalyst A33, amine catalyst A1, antibacterial microcapsules, and modified hybrid nanoparticles are uniformly stirred using a high-speed disperser, and then diphenylmethane diisocyanate is added and stirred quickly, and then poured into a constant temperature mold, molded and foamed, and the mold is opened after 25 minutes to obtain the environmentally friendly sponge.
[0048] Comparative Example 1
[0049] An environmentally friendly sponge comprises the following raw materials in parts by weight: 130 parts of polyether polyol, 70 parts of diphenylmethane diisocyanate, 5 parts of diethanolamine, 8 parts of polyether polyol S25K, 4 parts of deionized water, 0.3 parts of silicone oil L-580, 1.5 parts of amine catalyst A33, 0.5 parts of amine catalyst A1, and 12 parts of modified hybrid nanoparticles; the modified hybrid nanoparticles are triazine derivative grafted nano-titanium dioxide-nano-zinc oxide hybrid particles prepared in Example 2;
[0050] The preparation method of the above-mentioned environmentally friendly sponge is the same as that of Example 5.
[0051] Comparative Example 2
[0052] An environmentally friendly sponge comprises the following raw materials in parts by weight: 130 parts of polyether polyol, 70 parts of diphenylmethane diisocyanate, 5 parts of diethanolamine, 8 parts of polyether polyol S25K, 4 parts of deionized water, 0.3 parts of silicone oil L-580, 1.5 parts of amine catalyst A33, 0.5 parts of amine catalyst A1, and 8 parts of antibacterial microcapsules; the antibacterial microcapsules are polyurea microcapsules containing benzyl benzoate and 1,2-benzisothiazol-3-one prepared by interfacial polymerization in Example 1;
[0053] The preparation method of the above-mentioned environmentally friendly sponge is the same as that of Example 5.
[0054] Performance Testing
[0055] 1. Aging resistance test
[0056] The environmentally friendly sponges in Examples 3 to 5 and Comparative Examples 1 to 2 were cut into test specimens, and the specimens were cut from the same latex sponge material, with a size of (6×3×1) cm. One group of each of the two specimens was hung together in a constant temperature and humidity chamber to ensure that they could be in good contact with the air and fully aged. The heat aging test was started under the following conditions: temperature 105°C, pressure saturated vapor pressure, and the resilience performance of the environmentally friendly sponge was measured according to GB / T 6670-2008 at aging time 0h, 24h, 48h, and 72h, and the rebound rate was calculated, rebound rate = (rebound height / compression depth) × 100%, and the results were shown in Table 1:
[0057] Table 1 Test results of environmentally friendly sponge aging resistance
[0058]
[0059] It can be seen from the data in Table 1 that after the accelerated aging test, the environmentally friendly sponges in Examples 3 to 5 and Comparative Example 1 still maintain a high rebound rate, indicating that the environmentally friendly sponges in Examples 3 to 5 and Comparative Example 1 have good aging resistance, while the modified hybrid nanoparticles are not added in Comparative Example 2, and its aging resistance is poor. The modified hybrid nanoparticles of the present invention are prepared by the nucleophilic substitution reaction of cyanuric chloride and 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl hydrazide and N-(2-aminoethyl)-3-aminopropyltriethoxysilane to prepare triazine derivatives, so that the triazine derivative molecules contain hindered phenol structure and siloxane structure, which are then grafted on the surface of nano-titanium dioxide-nano-zinc oxide hybrid particles, thereby improving the dispersibility of the hybrid nanoparticles in the polymer. At the same time, due to the presence of the hindered phenol structure, the material is given good thermal stability. In addition, the hybrid nanoparticles themselves have good light stability, which can also improve the aging resistance of the material.
[0060] 2. Antibacterial performance test
[0061] The antibacterial activity of the environmentally friendly sponges in Examples 3 to 5 and Comparative Examples 1 to 2 was determined by the plate colony counting method. Escherichia coli was cultured in Luria-Bertani (LB) medium and cultured overnight at 37°C and 150r / min with shaking. The obtained bacterial suspension was centrifuged and diluted with an appropriate amount of 0.9% NaCl solution. 100μl of the bacterial solution was added to a 96-well plate and measured using an ELISA reader. The Escherichia coli suspension was diluted to an optical density of OD600 = 0.1 (the colony forming unit was 108CFU / mL at this time), and then diluted to 105CFU / mL using NaCl solution. The environmentally friendly sponge sample was cut into a size of 10mm×10mm×5mm. After being sterilized by ultraviolet irradiation for 3 hours, the sample was placed in a 100mL bacterial suspension (10 5CFU / mL) in a conical flask, take out the bacterial solution at different time intervals (0, 1, 2, 4, 8h) and put it into the well plate, and add NaCl solution to dilute it to 10 3 CFU / mL. 100 μl of bacterial solution was applied to LB agar plate and cultured at 37°C for more than 16 hours. The colony plate test was performed at least three times independently. After determining the number of colonies, the inhibition rate was calculated according to the following formula: Inhibition rate (%) = mean number of colonies at a certain time / mean number of initial colonies × 100%, and the data obtained are shown in Table 2 below:
[0062] Table 2 Test results of antibacterial properties of environmentally friendly sponges
[0063]
[0064] It can be seen from the data in Table 2 that the environmentally friendly sponges in Examples 3 to 5 and Comparative Example 2 have good antibacterial properties. In Comparative Example 1, since no antibacterial microcapsules are added, the antibacterial rate is significantly lower than that of other groups. The polyurea-based antibacterial microcapsules synthesized by the interfacial polymerization method of the present invention have a high encapsulation rate of benzyl benzoate and 1,2-benzisothiazol-3-one. At the same time, the microcapsule wall material has good ultraviolet absorption performance and thermal stability, which can effectively protect the core material. The encapsulated microcapsules have good sustained release performance and can have a long-term mite removal effect and antibacterial properties.
[0065] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. An environmentally friendly sponge, characterized in that: The invention comprises the following raw materials in parts by weight: 110-150 parts of polyether polyol, 60-80 parts of diphenylmethane diisocyanate, 2-8 parts of crosslinking agent, 5-10 parts of cell opener, 3-5 parts of foaming agent, 0.1-0.5 parts of foam stabilizer, 1.5-2.5 parts of amine catalyst, 5-10 parts of antibacterial microcapsule and 10-15 parts of modified hybrid nanoparticles; The antibacterial microcapsules are polyurea microcapsules containing benzyl benzoate and 1,2-benzisothiazol-3-one prepared by interfacial polymerization; The modified hybrid nanoparticles are nano-titanium dioxide-nano-zinc oxide hybrid particles grafted with triazine derivatives, and the triazine derivative molecules contain hindered phenol structures and siloxane structures.
2. The environmentally friendly sponge according to claim 1, characterized in that: The polyether polyol has a number average molecular weight of 600 to 800, a functionality of 3, and a hydroxyl value of 230 to 250 mgKOH / g.
3. The environmentally friendly sponge according to claim 1, characterized in that: The cross-linking agent is diethanolamine, the cell opening agent is polyether polyol S25K, the foam stabilizer is silicone oil L-580, the amine catalyst is compounded by amine catalyst A33 and amine catalyst A1, and the foaming agent is deionized water.
4. The environmentally friendly sponge according to claim 1, characterized in that: The preparation method of the antibacterial microcapsules comprises the following steps: (1) Gum arabic is uniformly dispersed in deionized water and a stable aqueous phase is formed by magnetic stirring, and benzyl benzoate, 1,2-benzisothiazol-3-one and isophorone diisocyanate are mixed at room temperature to form an oil phase; (2) pouring the oil phase into the water phase for emulsification treatment, emulsifying by high-speed shearing at 6000-8000 r / min for 8-10 min to form a uniform water-in-oil emulsion, and then heating the obtained emulsion to 30° C. while continuously stirring, and then adding 1,6-hexanediamine; (3) keeping the mixture at 30° C. for 20 to 30 minutes, then raising the temperature to 60° C. for reaction for 2 to 4 hours, and after the reaction, washing the mixture with 20% Vol ethanol aqueous solution and deionized water in sequence, followed by filtering and freeze-drying to obtain the antibacterial microcapsules.
5. The environmentally friendly sponge according to claim 4, characterized in that: The mass ratio of the gum arabic, benzyl benzoate and 1,2-benzisothiazol-3-one is 1:3.4-3.8:0.2-0.
6.
6. The environmentally friendly sponge according to claim 1, characterized in that: The preparation method of the modified hybrid nanoparticles comprises the following steps: A. Add nano titanium dioxide powder to ionized water, ultrasonically disperse for 5 to 10 minutes, then add zinc nitrate hexahydrate and sodium dodecylbenzene sulfonate, continue ultrasonically dispersing for 40 to 60 minutes, add 3wt% urea solution, and heat at 80°C for 1 to 3 hours. After filtering and washing the product, place it in a 350°C tubular furnace and calcine it for 3 to 5 hours to obtain nano titanium dioxide-nano zinc oxide hybrid particles; B. Add cyanuric chloride to tetrahydrofuran and triethylamine under nitrogen atmosphere, stir to dissolve cyanuric chloride, then uniformly add 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionohydrazide, react in an ice bath for 6-8 hours after the addition is completed, then add N-(2-aminoethyl)-3-aminopropyltriethoxysilane dropwise to the reaction system, then heat up to 60°C at a rate of 2-4°C / min, keep the temperature for 3-5 hours, cool after the reaction is completed, remove triethylamine hydrochloride by suction filtration, remove tetrahydrofuran by reduced pressure distillation, wash with deionized water 3-5 times, add ethyl acetate to the separated organic phase, dry and filter, and distill the filtrate under reduced pressure to obtain a triazine derivative; C. Add nano-titanium dioxide-nano-zinc oxide hybrid particles to an ethanol aqueous solution, ultrasonically disperse for 10 to 15 minutes, adjust the solution pH to 4 with a hydrochloric acid aqueous solution, then slowly add the triazine derivative to the above dispersion, continue ultrasonically dispersing for 5 to 10 minutes, heat to 80°C and keep warm for 3 to 5 hours, filter after cooling, wash, and dry to obtain the modified hybrid nanoparticles.
7. The environmentally friendly sponge according to claim 6, characterized in that: The mass ratio of the nano titanium dioxide, zinc nitrate hexahydrate and sodium dodecylbenzene sulfonate is 1:5 to 6:
3.
8. The environmentally friendly sponge according to claim 6, characterized in that: The molar ratio of cyanuric chloride, 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl hydrazide and N-(2-aminoethyl)-3-aminopropyltriethoxysilane is 1:2:1-2.
9. The environmentally friendly sponge according to claim 1, characterized in that: The preparation method of the environmentally friendly sponge comprises the following steps: polyether polyol, crosslinking agent, pore opening agent, foaming agent, foam stabilizer, amine catalyst, antibacterial microcapsule and modified hybrid nanoparticles are uniformly stirred by a high-speed disperser, then diphenylmethane diisocyanate is added, stirred rapidly, poured into a constant temperature mold, molded and foamed, and opened after 20 to 30 minutes to obtain the environmentally friendly sponge.
10. The use of the environmentally friendly sponge according to any one of claims 1 to 9, characterized in that: The environmentally friendly sponge is used in a slow-rebound sponge mattress and has good antibacterial and mite-removing effects.
Citation Information
Patent Citations
Water-based two-component polyurethane varnish and preparation process thereof
CN118725714A
Acrylic polymer water-based paint and preparation method thereof
CN118791920A
Cited By
Slow-resilience sponge material formula and manufacturing process thereof
CN120158078A